Associations between alcohol use and peripheral, genetic, and epigenetic markers of oxytocin in a general sample of young and older adults. Issue 3 (11th February 2022) - Rung, Jillian M.; Kidder, Quintin A.; Horta, Marilyn; Nazarloo, H. P.; Carter, C. Sue; Berry, Meredith S.; Ebner, Natalie C.
Abstract: Introduction: Human and nonhuman animal research suggests that greater oxytocin (OT) activity is protective against harmful substance use. Most research on this topic is preclinical, with few studies evaluating the association between substance use and individual differences in the human OT system. The present study sought to fill this gap by evaluating the relationship between alcohol use and multiple biological measures of OT activity in an overall low to moderate‐drinking sample. Method: As part of a larger study, generally healthy young ( n  = 51) and older ( n  = 53) adults self‐reported whether they regularly used alcohol and how much alcohol they consumed per week. Participants also provided blood samples from which peripheral OT, and in an age‐heterogeneous subset of participants ( n  = 56) variation in the oxytocin receptor gene (the OXTR rs53576 polymorphism) and OXTR DNA methylation levels (at cytosine–guanine dinucleotide sites ‐860, ‐924, ‐934), were obtained. Results: A‐allele carriers of the OXTR rs53579 polymorphism were less likely to regularly consume alcohol. Among regular alcohol consumers, number of alcoholic drinks per week was positively associated with peripheral OT in regression models excluding observations of high influence (postdiagnostic models). Number of alcoholic drinks per week was consistently negatively associated with OXTR DNA methylation at site ‐860; and with OXTR DNA methylation at site ‐924 in postdiagnostic models. Conclusions: The significant associations between alcohol use and individual differences in OT activity support the involvement of the OT system in alcohol use, which most likely reflect the role of OT when alcohol use is under control of its rewarding properties and/or the acute impacts of alcohol on the OT system. Additional research with markers of OT activity and alcohol use, particularly longitudinal, is needed to clarify the bidirectional effects of OT and alcohol use in moderate to harmful drinking and dependence. Abstract : Multiple measures thought to be indicative of lower oxytocin activity were associated with less frequent (i.e., non‐regular consumption) and fewer alcoholic beverages consumed per week in younger and older adult humans engaging in generally low to moderate alcohol use. These associations were most robust between regular alcohol use and variation in the oxytocin receptor gene (the rs53576 polymorphism); and degree of oxytocin receptor gene DNA methylation at specific sites and quantities of alcohol consumed.